COMBINATION EFFECT OF MANGO LEAF WATER EXTRACT (Mangifera indicaL.) AND CHINESE BETEL LEA VES (Peperomia pellucidaL. Kunth) ON BLOOD SUGAR LEVELS OF MALE WHITE RATS (Rattus norvegicus) DIABETES MELLITUS TYPE 2: COMBINATION EFFECT OF MANGO LEAF WATER EXTRACT (Mangifera indicaL.) AND CHINESE BETEL LEA VES (Peperomia pellucidaL. Kunth) ON BLOOD SUGAR LEVELS OF MALE WHITE RATS (Rattus norvegicus) DIABETES MELLITUS TYPE 2 - Penina Triyanti Simalango (Universitas Methodist Indonesia, 2025)
BackgroundDiabetes mellitus (DM) is a disease caused by a metabolic disorder that occurs in the pancreatic duct. DM is characterized by elevated blood sugar levels (BGD), often referred to as hyperglycemia. This condition occurs when the pancreas reduces total insulin production. Research methods: this observation is of an experimental laboratory character using a research designpost test only controlled group designin male white mice with type 2 diabetes mellitus (DMT2). Results: The p-value for the initial KGD was <0.138, the p-value for the KGD in the first week of HFD administration was <0.310, the p-value for the KGD in the 2nd week of HFD administration was <0.378, the p-value for the KGD in the 3rd week of HFD administration was <0.333, the p-value for the KGD in the 4th week of HFD administration was <0.241. Conclusion: The combination of mango leaf water extract at a dose of 200 mg/kgBW and Chinese betel leaf at a dose of 200 mg/kgBW was more effective in reducing blood glucose compared to the other groups. Keywords: Diabetes Mellitus, Blood Sugar Levels, High Fatty Diet BackgroundDiabetes mellitus (DM) is a disease caused by a metabolic disorder that occurs in the pancreatic duct. DM is characterized by elevated blood sugar levels (BGD), often referred to as hyperglycemia. This condition occurs when the pancreas reduces total insulin production. Research methods: this observation is of an experimental laboratory character using a research designpost test only controlled group designin male white mice with type 2 diabetes mellitus (DMT2). Results: The p-value for the initial KGD was <0.138, the p-value for the KGD in the first week of HFD administration was <0.310, the p-value for the KGD in the 2nd week of HFD administration was <0.378, the p-value for the KGD in the 3rd week of HFD administration was <0.333, the p-value for the KGD in the 4th week of HFD administration was <0.241. Conclusion: The combination of mango leaf water extract at a dose of 200 mg/kgBW and Chinese betel leaf at a dose of 200 mg/kgBW was more effective in reducing blood glucose compared to the other groups. Keywords: Diabetes Mellitus, Blood Sugar Levels, High Fatty Diet